2017
DOI: 10.1097/md.0000000000008030
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and burnout of emergency professionals of a health region

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 21 publications
9
52
2
5
Order By: Relevance
“…On the other hand, the investigation of Ravalier et al [30] observed that emotional exhaustion and depersonalisation increased in the second survey, but that personal accomplishment also increased, although the data analysed were from 2012. Our data from 2018 give similar scores to those obtained in a study undertaken of emergency doctors and nurses in a province of Catalonia in 2017 [32], although the score in the professional accomplishment dimension was higher than that of our study.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the investigation of Ravalier et al [30] observed that emotional exhaustion and depersonalisation increased in the second survey, but that personal accomplishment also increased, although the data analysed were from 2012. Our data from 2018 give similar scores to those obtained in a study undertaken of emergency doctors and nurses in a province of Catalonia in 2017 [32], although the score in the professional accomplishment dimension was higher than that of our study.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, it has suggested a reduction in professional burnout, which can help maintain the levels of empathy of high-level emergency professionals, which in turn will ensure a better quality of care. 10 Another study, which evaluated the relationship between empathy of nursing professionals and well-being, observed that emergency nurses appear to have low levels of empathy, in addition to perceiving in this professional class elevated levels of psychological suffering and low well-being. Empathy and well-being seem to be related, as higher empathy scores were found in nurses with higher well-being.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Indeed skills that improve healthcare professionals’ empathic capacity have been shown to be associated with lower levels of burnout. 18 19 20 The theory is that when healthcare professionals understand and communicate patients’ situations better, they feel more fulfilled, and they help to humanise care delivery, both of which are fundamental elements in the prevention of burnout. 21 Since the degree of burnout or professional stress can affect the quality of communication with the patient, this study is particularly relevant given that healthcare professionals are being subjected to increasing clinical workloads and greater time constraints.…”
Section: Introductionmentioning
confidence: 99%